Late reaction, persistent reaction and doubtful allergic reaction: The problems of interpretation - Sarma Nilendu (Wolters Kluwer Medknow Publications, 2009)
The standard method of patch test reading is to read the test site for any positive allergy at 48hr and then again at 72/96 hr. A late reading on the seventh day is also advised to exclude the irritant reaction (IR) and to notice some delayed development of allergic reaction. However, multiple visits are often difficult for the patient; therefore, this late reading is sometimes omitted. Here a case of plantar hyperkeratosis, due to allergic contact dermatitis, is reported with some insight into interpretation of the patch test. The patient showed delayed patch test reaction to formaldehyde and colophony, which has never been reported before.